Geographic variation in population structure and grazing features of Calanus glacialis/marshallae in the Pacific Arctic Ocean - Ishihara, Minami; Matsuno, Kohei; Tokuhiro, Koki; Ando, Yasuhiro; Sato, Kazutoshi; Yamaguchi, Atsushi (Frontiers in Marine Science, 2023)
Calanus glacialis/marshallae is a dominant zooplankton species in the Pacific Arctic Ocean that is widely distributed in shelf areas, and it plays a vital role in connecting primary production to higher trophic levels. Its phenology is well adapted to hydrography, but there is little available information about regional and diel changes in population structure and grazing features. In this study, we investigated C. glacialis/marshallae during autumn 2019 in the Eastern and Northeastern Chukchi and Canadian basins to reveal geographic and diel variations in population structure, body size, grazing activity, and fatty acid composition. The abundance of C. glacialis/marshallae was found to be high on the slopes and low on the shelves. Body size (prosome length) was well described by the Bělehrádek equation combined with in-situ temperature throughout the sampling region. Cluster analyses based on hydrographic parameters were divided into four regions: southern shelf, northern shelf, slope, and basin. The southern shelf was dominated by copepodite stage five (C5) transported from the Bering Sea by Pacific waters. C4 and C5 were dominant on the northern shelf, suggesting that they grew slower than those on the southern shelf, and the populations also exhibited higher concentrations of fatty acids originating from dinoflagellates than those originating from the pan-Arctic Ocean, indicating low productivity in the region. The population on the slope had the highest abundance, C4 was dominant, and large amounts of diatom-derived eicosapentaenoic acid (EPA). These features are attributed to the upwelling of populations and nutrients that support diatom growth. In the basin, the early copepodite stages of composition were distinctly higher than those recorded in previous studies, because larger amounts of organisms flow into the region, resulting in more extended reproduction periods. In the basin, small and large forms of C5 were simultaneously found, and the small form exhibited a diel grazing activity pattern, but the large forms did not. These findings suggest their well adaptation in changing of the Pacific Arctic Ocean.